MENILAI NPL, BOPO, LDR MELALUI PROFITABILITAS - Mertyani Sari Dewi; Luh Luji Purnami (ARTHA SATYA DHARMA, 2021)
The purpose of this study was to determine the effect of NPL, BOPO, LDR on profitability at the Sari Mekar Traditional Village LPD. The research method used in this study is a quantitative method. Data collection techniques used in this study were documentation and interviews. The data analysis technique in this study used the classical assumption test consisting of normality test, multicollinearity test, heteroscedasticity test, and multiple linear regression analysis, analysis of determination (R2) and hypothesis testing (t test). Based on the results of the study, it can be concluded that: (1) Non-Performing Loans have a negative and insignificant effect on profitability, (2) Operational Costs of Operating Income have a negative and insignificant effect on profitability, (3) Loan to Deposit Ratio has a negative and insignificant effect on profitability.